In vivo oral toxicity and antioxidant capacity of Nothofagus antarctica (G.Forst.) oerst (ñire) leaves - Hugo, Ayelen Amelia; Serradell, María de los Ángeles; Peri, Pablo Luis; Farina, Sebastián; Gomez Zavaglia, Andrea (CyTA - Journal of Food)
Nothofagus antarctica (NA) is a native tree of Patagonia. Since ancient times, NA leaves were used in infusions for medical and food purposes, but there are no deep insights on its toxicity. The aim of this work was to assess the safety and antioxidant activity of NA leaves infusion. Mice were used to determine acute and subacute oral toxicity. Total polyphenols, flavonoids and the antioxidant activity of the infusion were assessed, as well as the antioxidant activity in biological samples. Toxicity tests revealed no death or signs of toxicity. No significant differences in biochemical parameters/histological structure were registered. NA infusion exhibited a high content of polyphenols and flavonoids, contributing to its remarkably antioxidant activity. The periodic administration of NA infusion could increase the antioxidant capacity in mice at intestinal level. The results support the safe of consuming NA leaves infusion and suggest their contribution for modulating the intestinal oxidative stress. Fil: Hugo, Ayelen Amelia. Provincia de Buenos Aires. Gobernación. Comisión de Investigaciones Científicas. Centro de Investigación y Desarrollo en Criotecnología de Alimentos. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigación y Desarrollo en Criotecnología de Alimentos. Universidad Nacional de La Plata. Facultad de Ciencias Exactas. Centro de Investigación y Desarrollo en Criotecnología de Alimentos; Argentina Fil: Serradell, María de los Ángeles. Provincia de Buenos Aires. Gobernación. Comisión de Investigaciones Científicas. Centro de Investigación y Desarrollo en Criotecnología de Alimentos. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigación y Desarrollo en Criotecnología de Alimentos. Universidad Nacional de La Plata. Facultad de Ciencias Exactas. Centro de Investigación y Desarrollo en Criotecnología de Alimentos; Argentina Fil: Peri, Pablo ...